"Community developed and farmer delivered." An analysis of the spatial and relational proximities of the Alternative Land Use Services program in Ontario. (June 2020) - Ouellet, F.; Mundler, P.; Dupras, J.; Ruiz, J.
Highlights: In Canada, the ALUS program supports conservation projects by financially compensating farmers for ecosystem services. Features of ALUS include a bottom-up approach: "farmer-to-farmer" method and community approach to conservation. A common set of values encourages member participation, fosters stakeholder confidence and facilitates coordination. ALUS shows its ability to well mobilize farmers and put their environmental values into action in a cost-effective manner. From a territorial perspective, ALUS has limited reach because it fails to fully activate geographic proximity. Abstract: In Canada, the Alternative Land Use Services (ALUS) program aims to support conservation projects by financially compensating farmers for ecosystem services. The program advocates a bottom-up approach that allows farmers to decide which projects to implement. In this respect, ALUS distinguishes itself from more traditional agri-environment schemes, which are often managed in a top-down fashion. Other unique features of the program include a governance structure based on stakeholder confidence; the provision of annual compensation to members for supplying ecosystem services; and a private, community-based approach to conservation. Using the proximity analysis framework, our research explores whether this model can reshape the values of farmers and encourage them to adopt and maintain environmentally friendly practices. Our results reveal a close proximity among ALUS members in terms of their values, both environmental and economic. However, the ALUS program fails to take full advantage of the geographic and organized proximity of its participants. Specifically, individual projects are not integrated into a spatially coordinated, collective strategy that could have a greater environmental impact. While ALUS has been successful in encouraging farmers to adopt new practices, it mostly attracts participants who already agree with the values it promotes. In this regard, the program is not very different from standard agri-environment schemes.